Wybrane aspekty obsługi klienta w sprzedaży wysyłkowej niemieckiego przedsiębiorstwa wydawniczego - Piasecka-Głuszak, Agnieszka (Certain Aspects of Customer Service in Mail Order Business of German Publishing Company, 2005)
This article presents certain aspects of customer service in German publishing company operating on Polish market and involved among other things in mail order business. The author describes shortly the work of each section of Customer Service Department: orders processing section, correspondence section, telecommunication section, payments and returns section. Presents major measures that are analysed in examined Department. The emphasis is put on integrated attitude towards the customer which involves the appropriate availability for the customer, the appropriate level of customer service, the appropriate attitude and way of communication with the customer.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 381-389